Plasma levels of tissue inhibitor of matrix metalloproteinase-1 correlate with diagnosis and prognosis of glioma patients - LIN, Yi; WANG, Jiang-Fei; GAO, Guang-Zu; ZHANG, Guo-Zhen; WANG, Fei-Long; WANG, Yun-Jie (Chinese medical journal, 2013)
Background There is no validated blood biomarker available for glioma management. Invasive growth is the key feature of glioma. We assessed the clinical usefulness of plasma tissue inhibitor of metalloproteinase 1 （TIMP-1）, which has less molecular weight than metalloproteinases, as a potential blood biomarker for glioma. Methods A total of 285 patients and 59 normal subjects were studied. Plasma concentration of TIMP-1 was measured with enzyme-linked immunosorbent assay. Plasma TIMP-1 was compared between normal and glioma patients, between patients with different pathological grades, and between patients with different prognoses. Longitudinal changes in plasma TIMP-1 during treatment were also evaluated. Plasma matrix metalloproteinase （MMP）-9 level was also assayed and its clinical usefulness was compared with that of TIMP-1. Results Plasma TIMP-1 and MMP-9 were both increased in glioma patients compared with normal controls （TIMP-1： P 〈0.001; MMP-9： P=0.007）. Plasma TIMP-1 increases with increased tumor grade. In Grade Ⅳ gliomas, plasma TIMP- 1 significantly increased after ＂successful removal＂ of the tumor （paired samples t-test, before operation vs. during chemotherapy without recurrence, t = -2.131, P=0.038）, but did not change significantly at the time of tumor recurrence （during chemotherapy without recurrence vs. after tumor recurrence, t = -0.652, P=-0.632）. High plasma TIMP-1 level correlated with better survival in Grade IV glioma patients （hazard ratio： 0.550, 95% CI： 0.101-1.000, P=0.036）. In Grade IV gliomas, patients with higher plasma TIMP-1 had significantly longer survival time than those with lower plasma TIMP-1 level （25.23 vs. 18.95 months, log-rank P=0.045）. Plasma MMP-9 did not show significant association with either the pathological grade or the prognosis of glioma patients. Conclusions Plasma TIMP-1 is associated with the diagnosis and prognosis of glioma patients. It appears to have better usefulness for guiding clinical decision making than plasma MMP-9. Further studies in an expanded patient population are needed to better define its clinical usefulness.